Measuring validity and reliability of the Italian version of Physical Activity Questionnaire for Older Children in overweight and obese children - Monacis, Domenico; Annoscia, Sabrina; Colella, Dario; Limone, Pierpaolo (Frontiers in Education, 2024)
The measure of daily physical activity (PA) is one of the most important topics in the field of health promotion. In addition, self-efficacy and enjoyment are significant factors that can foster adherence to physical activity during a person’s lifetime. The present study aims to assess the validity and reliability of Physical Activity Questionnaire for Older Children-Italian version (PAQ-C-It) in a sample of normal weight, overweight, and obese children. Three studies were conducted to assess the (1) general characteristics of PAQ-C-It, (2) model fit and construct validity between PA, self-efficacy, and enjoyment, and (3) reliability and construct validity of PAQ-C-It in normal weight, overweight, and obese children. The sample involved a total of 914, 500, and 600 children (male = 466, female = 448) attending first grade of secondary school (age = 11–13 years), in the first, second and third study, respectively. Children were asked to respond to three scales: Physical Activity Questionnaire for Older Children (PAQ-C-It), the Perceived Physical Ability Scale (PPAS), and Physical Activity Enjoyment Scale (PACES). Then, explorative and confirmatory factor analyses were conducted to assess the validity and reliability of the PAQ-C-It by relating results with those of the other scales. The analysis showed acceptable value and internal consistency of items for the subscales (α > 0.7), as well as the average variance extracted (>0.5) in both normal weight, overweight, and obese children. The results of the present study show that PAQ-C-It can be applied in the field of physical activity to measure adherence to physical activity and healthy behaviors. Moreover, self-efficacy and enjoyment are significant factors that can best promote adherence to PA. The present study can extend our knowledge about PAQ-C-It and open up new research avenues for driving interventions aimed at reducing sedentary behavior and improving PA in overweight and obese children.